Cobalt-coated carbonyl iron powder as well as preparation method and application thereof
Through cobalt coating technology, the problem of insufficient oxidation resistance and corrosion resistance of sheet carbonyl iron powder is solved, and its wave absorption performance and stability are significantly improved. It is suitable for electromagnetic wave shielding applications in various frequency bands.
Patent Information
- Application Number
- CN202411193039.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-28
- Publication Date
- 2024-12-27
AI Technical Summary
The prior art is difficult to effectively modify the oxidation resistance and corrosion resistance of sheet-shaped carbonyl iron powder, especially in high frequency bands, which leads to its oxidation easily at high temperatures and affects its wave absorption performance.
Using cobalt coating technology, cobalt plating solution is formed by mixing cobalt salt, reducing salt, active agent and complexing agent, adding carbonyl iron powder and conducting insulation reaction, controlling the pH between 9.5 and 10.5 to form a uniform and complete cobalt plating Covering to improve its impedance matching characteristics and absorbance properties.
It significantly improves the wave absorption and oxidation resistance of carbonyl iron powder, extends the initial oxidation temperature, is suitable for sheet and spherical powders, and enhances the stability of the material and electromagnetic wave shielding ability.
Smart Images

Figure CN119187559A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of advanced materials, and in particular relates to a cobalt-coated carbonyl iron powder and a preparation method and application thereof. Background Art
[0002] In recent years, against the background of rapid development in the field of national defense aviation, the rapid development of radar technology has greatly improved the ability and efficiency of electromagnetic waves in detecting military targets such as aircraft and ships. Aircraft with electromagnetic wave absorption technology is the core of anti-reconnaissance of weapons and equipment, which has higher requirements for the materials used in aircraft. Due to its application in electromagnetic interference shielding (EMI) and reducing radar cross section (RCS), absorbing materials have attracted more and more attention. At present, the research focuses on the design and modification of existing absorbing materials, and is committed to the innovative research and development of new absorbing materials, aiming to develop new electromagnetic absorbing materials with wide frequency band, strong corrosion resistance, good compatibility and excellent mechanical properties. This is the core research direction in the field of electromagnetic wave shielding technology.
[0003] High saturation magnetization, high initial magnetic permeability, excellent magnetic loss capacity and electrical conductivity, these characteristics make magnetic metal powder show efficient wave absorption ability in the microwave frequency band, and become the focus of magnetic wave absorbing material research. Furthermore, as the earliest researched, mature process and widely used radar absorber, carbonyl iron powder has low density, high dielectric loss, high magnetic loss and good impedance matching characteristics, which are suitable for applications in a wide frequency range. For carbonyl iron powder, spherical powder has high density and high magnetic loss, and the high-frequency wave absorption performance is optimized by adjusting the ball milling process parameters; although the flaky powder has a larger surface area, which is conducive to high-frequency wave absorption, it is easily affected by oxidation, and attention should be paid to the increase in dielectric constant and impedance matching caused by interface polarization.
[0004] Since carbonyl iron powder is easily oxidized at high temperatures (the initial oxidation temperature is about 200°C, which is much lower than the Curie temperature of 770°C), especially flake powder, the increase in surface area exacerbates this problem, requiring modification to improve oxidation resistance and corrosion resistance, while controlling the dielectric constant to ensure long-term stability and wave absorption performance. In the material preparation process, Co (cobalt) coating is a feasible modification method used to improve the performance of the material, such as improving oxidation resistance and conductivity. Traditional Co coating technology is more used in spherical carbonyl iron powder because spherical powder has a smaller specific surface area, which is conducive to the uniform distribution of the coating material. However, when trying to apply this technology to flaky carbonyl iron powder, challenges were encountered, mainly because the specific surface area of flaky powder is relatively large, resulting in poor coating effect. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a cobalt-coated carbonyl iron powder and a preparation method and application thereof. The coating method proposed in the present invention is suitable for flake and spherical carbonyl iron powders, and the obtained Co coating layer exhibits excellent uniformity and integrity, which significantly improves the impedance matching characteristics of the Co-coated carbonyl iron powder, thereby enhancing the microwave absorption performance of the carbonyl iron powder.
[0006] The purpose of the present invention is achieved through the following technical solutions: A method for preparing cobalt-coated carbonyl iron powder comprises the following steps: (1) mixing a cobalt salt, a reducing salt, an active agent and a complexing agent, and adding a solvent to prepare a cobalt plating solution, wherein the concentration of the reducing salt in the cobalt plating solution is 25-45 g / L; (2) heating the cobalt plating solution to 70-90° C. and adjusting the pH to 9.5-10.5, then adding carbonyl iron powder and carrying out a heat-insulating reaction, wherein the pH is controlled to be 9.5-10.5 during the reaction; (3) After the heat preservation reaction is completed, the powder is separated and washed and dried to obtain the cobalt-coated carbonyl iron powder.
[0007] Preferably, in step (1), the cobalt salt is at least one of cobalt sulfate, cobalt chloride, cobalt nitrate and hydrates thereof.
[0008] Preferably, in step (1), the reducing salt is at least one of sodium hypophosphite, sodium borohydride and alkylamine borane.
[0009] Preferably, in step (1), the complexing agent is at least one of sodium citrate, sodium tartrate and their hydrates.
[0010] Preferably, in step (1), the active agent is ammonium chloride.
[0011] Preferably, in step (1), the solvent is at least one of water and ethanol.
[0012] Preferably, in step (1), the concentration of the cobalt salt in the cobalt plating solution is 10-50 g / L.
[0013] Preferably, in step (1), the concentration of the activator in the cobalt plating solution is 30-60 g / L.
[0014] Preferably, in step (1), the concentration of the complexing agent in the cobalt plating solution is 20-100 g / L.
[0015] Preferably, in step (2), after the cobalt plating solution is heated to 70-90° C., the pH is adjusted to 9.5-10.5 by adding sodium hydroxide.
[0016] Preferably, in step (2), the carbonyl iron powder is flaky carbonyl iron powder or spherical carbonyl iron powder.
[0017] Preferably, in step (2), the cobalt plating solution is heated to 70-90° C. by water bath heating.
[0018] Preferably, in step (2), during the heat preservation reaction, the pH of the reaction process is controlled to be 9.5-10.5 by adding acidic and alkaline substances, wherein the alkaline substance is at least one of NaOH, KOH, Ca(OH)2 and ammonia water; and the acidic substance is at least one of citric acid, acetic acid, dilute HCl, dilute H2SO4 and dilute HNO3.
[0019] Preferably, in step (2), the amount of carbonyl iron powder added to the cobalt plating solution is 5-10 g / L.
[0020] Preferably, in step (2), carbonyl iron powder is added under stirring conditions at a stirring rate of 300-600 rmp.
[0021] Stirring has the following two main purposes: one is to ensure the uniform distribution of carbonyl iron powder in the plating solution, and the other is to promote the uniform deposition of cobalt on the surface of carbonyl iron powder.
[0022] Preferably, in step (2), the insulation reaction time is 60 to 180 min, and more preferably, the insulation reaction time is 90 to 120 min.
[0023] Preferably, in step (3), the specific steps of separating the powder are: after the insulation reaction is completed, distilled water is added to the reaction container, and the iron powder is adsorbed to the bottom of the container by a magnet; then, the distilled water on the upper layer is poured out to separate and retain the iron powder, that is, the powder is separated by a magnet.
[0024] Preferably, in step (3), the washing method is: first washing with distilled water and then washing with anhydrous ethanol.
[0025] Preferably, in step (3), drying is vacuum drying.
[0026] The cobalt-coated carbonyl iron powder prepared by the method for preparing the cobalt-coated carbonyl iron powder.
[0027] Application of the above cobalt-coated carbonyl iron powder in the preparation of microwave absorbing materials.
[0028] The reaction principles involved in the present invention are: Through further research, the applicant found that the process of Co reduction requires OH -If the pH value is adjusted by adding NaOH only at the beginning of the experiment, the overall pH value of the solution will drop to a neutral or slightly acidic level after a period of time, which is not conducive to the further progress of the experiment. Therefore, it is necessary to dynamically adjust the pH value during the experiment and keep the solution in an alkaline environment.
[0029] The reactions involved in the present invention are as follows: Reduction of Co:
[0030] Reduction of P:
[0031] Generation of H2: .
[0032] Compared with the prior art, the beneficial effects of the present invention include: The coating method proposed in the present invention is applicable to flake and spherical carbonyl iron powders, and the obtained Co coating layer exhibits excellent uniformity and integrity, which significantly improves the impedance matching characteristics of the Co-coated carbonyl iron powder, thereby enhancing the microwave absorption performance of the carbonyl iron powder. In addition, the initial oxidation temperature of the carbonyl iron powder after Co coating is also delayed by 120-140°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is the EDS surface scan of the cobalt-coated carbonyl iron powder prepared in Example 1.
[0034] Figure 2 XRD diffraction patterns of the cobalt-coated carbonyl iron powder prepared in Example 1 before and after coating.
[0035] Figure 3 This is a reflection loss diagram of the cobalt-coated carbonyl iron powder prepared in Example 1 before and after coating.
[0036] Figure 4 This is a graph showing the oxidation kinetics of the cobalt-coated carbonyl iron powder prepared in Example 1 before and after coating.
[0037] Figure 5 This is the EDS surface scan of the cobalt-coated carbonyl iron powder prepared in Example 2.
[0038] Figure 6 This is a cross-sectional morphology of the cobalt-coated spherical carbonyl iron powder prepared in Example 2.
[0039] Figure 7 This is a graph showing the oxidation kinetics of the cobalt-coated carbonyl iron powder prepared in Example 2 before and after coating.
[0040] Figure 8This is the surface morphology of the cobalt-coated flaky carbonyl iron powder described in Example 3.
[0041] Fig. 9 This is a scanning electron microscope image of the cobalt-coated carbonyl iron powder prepared in Comparative Example 1.
[0042] Fig.10 This is the EDS surface scan of the cobalt-coated carbonyl iron powder prepared in Comparative Example 2. DETAILED DESCRIPTION
[0043] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0044] The flaky carbonyl iron powder used in the examples and comparative examples was prepared according to the method disclosed in the article "Study on the Effect of Ball Milling Steel Bead Ratio on the Absorption Performance of Flaky Carbonyl Iron Powder" published in the Journal of Aeronautical Materials, Issue 5, 2013.
[0045] The spherical carbonyl iron powder described in the examples and comparative examples was purchased from Shaanxi Xinghua Group Co., Ltd.
[0046] Example 1 A method for preparing cobalt-coated carbonyl iron powder, comprising the following steps: (1) Cobalt sulfate, sodium hypophosphite, ammonium chloride and sodium citrate are mixed and water is added to prepare a cobalt plating solution, wherein the concentration of sodium hypophosphite in the cobalt plating solution is 45 g / L; the concentration of cobalt sulfate is 20 g / L; the concentration of ammonium chloride is 40 g / L; and the concentration of trisodium citrate is 50 g / L; (2) heating the cobalt plating solution to 90° C. in a water bath, adjusting the pH to 9.5 by adding sodium hydroxide, then adding flaky carbonyl iron powder while stirring and carrying out a heat-insulating reaction, wherein the amount of flaky carbonyl iron powder added is 5 g / L, and the pH is controlled to be 9.5 during the reaction; (3) After the heat preservation reaction is completed for 120 minutes, distilled water is added to the reaction container, and the iron powder is adsorbed to the bottom of the container by a magnet; then, the distilled water on the upper layer is poured out to separate and retain the powder. The powder is first washed twice with distilled water and then washed twice with anhydrous ethanol. After washing, the powder is separated by a magnet according to the above method, and finally vacuum dried to obtain the cobalt-coated carbonyl iron powder.
[0047] Example 2 A method for preparing cobalt-coated carbonyl iron powder, comprising the following steps: (1) Cobalt sulfate, sodium hypophosphite, ammonium chloride and sodium citrate are mixed and water is added to prepare a cobalt plating solution, wherein the concentration of sodium hypophosphite in the cobalt plating solution is 25 g / L; the concentration of cobalt sulfate is 20 g / L; the concentration of ammonium chloride is 40 g / L; and the concentration of trisodium citrate is 50 g / L; (2) heating the cobalt plating solution to 70° C. in a water bath, adjusting the pH to 10.5 by adding sodium hydroxide, then adding spherical carbonyl iron powder while stirring and carrying out a heat-insulating reaction, wherein the amount of spherical carbonyl iron powder added is 10 g / L, and the pH is controlled to be 10.5 during the reaction; (3) After the heat preservation reaction is completed for 90 minutes, distilled water is added to the reaction container, and the iron powder is adsorbed to the bottom of the container by a magnet; then, the distilled water on the upper layer is poured out to separate and retain the powder. The powder is first washed twice with distilled water and then washed twice with anhydrous ethanol. After washing, the powder is separated by a magnet according to the above method, and finally vacuum dried to obtain the cobalt-coated carbonyl iron powder.
[0048] Example 3 A method for preparing cobalt-coated carbonyl iron powder, comprising the following steps: (1) Cobalt sulfate, sodium hypophosphite, ammonium chloride and sodium citrate are mixed and water is added to prepare a cobalt plating solution, wherein the concentration of sodium hypophosphite in the cobalt plating solution is 35 g / L; the concentration of cobalt sulfate is 20 g / L; the concentration of ammonium chloride is 40 g / L; and the concentration of trisodium citrate is 50 g / L; (2) heating the cobalt plating solution to 80° C. in a water bath, adjusting the pH to 10 by adding sodium hydroxide, setting the stirring rate to 300 rpm, then adding flaky carbonyl iron powder while stirring and carrying out a heat-insulating reaction, wherein the amount of flaky carbonyl iron powder added is 8 g / L, and the pH is controlled to be 10 during the reaction; (3) After the heat-insulating reaction is completed for 120 min, distilled water is added to the reaction container, and the iron powder is adsorbed to the bottom of the container using a magnet; then, the distilled water on the upper layer is poured out to separate and retain the powder. The powder is first washed twice with distilled water and then washed twice with anhydrous ethanol. After washing, the powder is separated using a magnet according to the aforementioned method, and finally vacuum dried to obtain the cobalt-coated carbonyl iron powder.
[0049] Comparative Example 1 A method for preparing cobalt-coated carbonyl iron powder, comprising the following steps: (1) Cobalt sulfate, sodium hypophosphite, ammonium chloride and sodium citrate are mixed and water is added to prepare a cobalt plating solution, wherein the concentration of sodium hypophosphite in the cobalt plating solution is 25 g / L; the concentration of cobalt sulfate is 20 g / L; the concentration of ammonium chloride is 40 g / L; and the concentration of trisodium citrate is 50 g / L; (2) heating the cobalt plating solution to 70° C. in a water bath, adjusting the pH to 6 with citric acid, then adding spherical carbonyl iron powder while stirring and carrying out a heat-insulating reaction, wherein the amount of spherical carbonyl iron powder added is 10 g / L; (3) After the heat preservation reaction is completed for 120 minutes, distilled water is added to the reaction container, and the iron powder is adsorbed to the bottom of the container by a magnet; then, the distilled water on the upper layer is poured out to separate and retain the powder. The powder is first washed twice with distilled water and then washed twice with anhydrous ethanol. After washing, the powder is separated by a magnet according to the above method, and finally vacuum dried to obtain the cobalt-coated carbonyl iron powder.
[0050] Comparative Example 2 A method for preparing cobalt-coated carbonyl iron powder, comprising the following steps: (1) Cobalt sulfate, sodium hypophosphite, ammonium chloride and sodium citrate are mixed and water is added to prepare a cobalt plating solution, wherein the concentration of sodium hypophosphite in the cobalt plating solution is 45 g / L; the concentration of cobalt sulfate is 20 g / L; the concentration of ammonium chloride is 40 g / L; and the concentration of trisodium citrate is 50 g / L; (2) heating the cobalt plating solution to 90° C. in a water bath, adjusting the pH to 9.5 by adding sodium hydroxide, then adding flaky carbonyl iron powder while stirring and carrying out a heat-insulating reaction, wherein the amount of flaky carbonyl iron powder added is 5 g / L, and the pH is not controlled during the reaction; (3) After the heat preservation reaction is completed for 120 minutes, distilled water is added to the reaction container, and the iron powder is adsorbed to the bottom of the container by a magnet; then, the distilled water on the upper layer is poured out to separate and retain the powder. The powder is first washed twice with distilled water and then washed twice with anhydrous ethanol. After washing, the powder is separated by a magnet according to the above method, and finally vacuum dried to obtain the cobalt-coated carbonyl iron powder.
[0051] The surface composition analysis of the cobalt-coated carbonyl iron powder prepared in Example 1 is performed, and the analysis results are shown in Table 1.
[0052] Table 1 Elemental composition analysis of the surface of the cobalt-coated carbonyl iron powder described in Example 1
[0053] The statistics in Table 1 show that the Co content is 58.57%, which strongly proves that Co is successfully deposited on the Fe surface.
[0054] Figure 1 This is the EDS scan of the cobalt-coated carbonyl iron powder prepared in Example 1. Figure 1It can be seen that the Co element is evenly distributed and has good contrast on the surface of the carbonyl iron powder, which qualitatively confirms that a complete and dense cobalt layer has been successfully coated on the surface of the carbonyl iron powder. It is particularly noteworthy that, given that the flaky carbonyl iron powder has a higher specific surface area than the spherical powder, especially the higher activity of the edge part and the relatively lower activity of the plane area, increasing the concentration of the reducing salt is a necessary strategy to promote the formation of a more uniform and comprehensive Co coating layer on the surface of the flaky powder, thereby optimizing the coating effect.
[0055] Figure 2 The XRD diffraction patterns of the cobalt-coated carbonyl iron powder prepared in Example 1 before and after coating, where CIP represents carbonyl iron powder (before coating) and CIP@Co represents cobalt-coated carbonyl iron powder (after coating). Figure 2 It can be seen that before coating, the main phase of the powder is iron (Fe) phase; after coating, the main phase changes to coexistence of iron (Fe) phase and cobalt (Co) phase. In particular, the PDF card shows that the cobalt (Co) phase deposited on the surface of carbonyl iron presents a hexagonal close-packed (HCP) structure, and the deposition amount is significant, and the phase characteristics are obvious.
[0056] Figure 3 The reflection loss diagram of the cobalt-coated carbonyl iron powder prepared in Example 1 before and after coating. Figure 3 It can be seen that after the coating treatment, the wave absorption performance of the carbonyl iron powder has been significantly enhanced. Specifically, in the uncoated state, the wave absorption ability of the flaky carbonyl iron powder shows an absorption peak of -12.65dB when its thickness is 2 mm. After the coating treatment, under the same test conditions, the absorption peak of the powder is greatly reduced to -21.15dB. This result shows that the coating process effectively improves the ability of carbonyl iron powder to absorb electromagnetic waves.
[0057] Figure 4 The oxidation kinetics curves of the cobalt-coated carbonyl iron powder prepared in Example 1 before and after coating are shown in FIG. Figure 4 It can be seen that the initial oxidation temperature of the uncoated flaky carbonyl iron powder is around 260°C, and the initial oxidation temperature of the carbonyl iron powder after Co coating is 380°C. It can be seen that the initial oxidation temperature is delayed by about 120°C after Co plating.
[0058] Figure 5 This is the EDS scan of the cobalt-coated carbonyl iron powder prepared in Example 2. Figure 5It can be seen that the surface of all powder particles within the visible range shows the presence of Co element. As shown in the figure, all carbonyl iron powder surfaces are completely covered with a cellular structure of Co coating layer. Furthermore, the surface scanning image reveals that the content of Co element is significantly higher than that of Fe element, which not only suggests that the Co coating layer has a certain thickness, but also shows that the coating process has a very ideal covering effect on the iron powder, that is, the Co coating layer shows excellent uniformity and consistency on a macro scale.
[0059] The surface composition analysis of the cobalt-coated carbonyl iron powder prepared in Example 2 is performed, and the analysis results are shown in Table 2.
[0060] Table 2 Elemental composition analysis of the surface of the cobalt-coated carbonyl iron powder described in Example 2
[0061] The statistics in Table 2 show that the Co content is 60.16%, which strongly proves that Co is successfully deposited on the Fe surface.
[0062] The wave absorption performance of the cobalt-coated carbonyl iron powder described in Example 2 was analyzed. When the thickness was 2.5 mm, the maximum absolute value of the electromagnetic wave loss peak of the uncoated carbonyl iron powder was -17.76 dB; while the wave absorption performance of the coated carbonyl iron powder (marked as CIP@Co) was significantly improved, and its maximum absolute value of the peak reached -19.39 dB.
[0063] Figure 6 This is a cross-sectional morphology of the cobalt-coated spherical carbonyl iron powder prepared in Example 2. Figure 6 It can be seen that the Co coating layer is evenly coated on the surface of the carbonyl iron powder, with a uniform thickness of about 300~350nm.
[0064] Figure 7 The oxidation kinetics curves of the cobalt-coated carbonyl iron powder prepared in Example 2 before and after coating are shown in FIG. Figure 7 It can be seen that the initial oxidation temperature of the uncoated spherical carbonyl iron powder is about 360° C., while the initial oxidation temperature of the carbonyl iron powder after Co coating is increased to 520° C. It can be seen that the Co plating treatment delays the initial oxidation temperature of the carbonyl iron powder by about 140° C.
[0065] Figure 8 This is the surface morphology of the cobalt-coated flaky carbonyl iron powder described in Example 3. Figure 8 It can be seen that due to the low mechanical stirring speed, some Co nanoparticles are deposited on the surface of the flaky carbonyl iron powder. Overall, the surface of the carbonyl iron powder is evenly coated with a layer of Co.
[0066] Fig. 9 This is a scanning electron microscope image of the cobalt-coated carbonyl iron powder prepared in Comparative Example 1. Fig. 9 It can be seen that the surface smoothness of the powder particles coated with Co in an acidic environment has significantly decreased, and instead has a rough feature, covered with a large number of fine cobalt particles, which are scattered on the surface in the form of protrusions. It is worth noting that the distribution of Co particles is not uniform. In some areas, clusters of Co particles are formed, while in other areas, the iron powder base is directly exposed and lacks the attachment of Co particles. This coating situation shows that for carbonyl iron powder, the coating effect is not good. The tiny Co particles are independent of each other, and they are not effectively connected to form a continuous and dense coating layer, which cannot provide comprehensive coverage protection for the carbonyl iron particles to effectively prevent the occurrence of oxidation.
[0067] Fig.10 This is the EDS scan of the cobalt-coated carbonyl iron powder prepared in Comparative Example 2. Fig.10 It can be seen that: when the pH of the reaction process is not controlled, as the chemical reaction gradually deepens, the pH environment in the system naturally evolves into a weak acid, and this change causes the reaction rate to drop significantly. As a result, the Co content is lower at the plane with lower surface activity of the powder. In contrast, the method of dynamic pH adjustment can maintain more ideal reaction conditions during the coating process, ensuring a more uniform distribution of Co on the powder surface and better consistency in the thickness of the coating layer. Therefore, the coated samples under non-dynamic pH control are inferior to the samples with dynamic pH adjustment in terms of the uniformity and thickness of the Co coating, especially in the planar areas with lower activity, where the lack of Co content is particularly prominent.
[0068] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing cobalt-coated carbonyl iron powder, characterized in that: The steps include: (1) mixing a cobalt salt, a reducing salt, an active agent and a complexing agent, and adding a solvent to prepare a cobalt plating solution, wherein the concentration of the reducing salt in the cobalt plating solution is 25-45 g / L; (2) heating the cobalt plating solution to 70-90° C. and adjusting the pH to 9.5-10.5, then adding carbonyl iron powder and carrying out a heat-insulating reaction, wherein the pH is controlled to be 9.5-10.5 during the reaction; (3) After the heat preservation reaction is completed, the powder is separated and washed and dried to obtain the cobalt-coated carbonyl iron powder.
2. The method for preparing cobalt-coated carbonyl iron powder according to claim 1, characterized in that: The cobalt salt in step (1) is at least one of cobalt sulfate, cobalt chloride, cobalt nitrate and hydrates thereof; The reducing salt in step (1) is at least one of sodium hypophosphite, sodium borohydride and alkylamine borane; the complexing agent in step (1) is at least one of sodium citrate, sodium tartrate and their hydrates; The active agent in step (1) is ammonium chloride; The solvent in step (1) is at least one of water and ethanol; The carbonyl iron powder in step (2) is flaky carbonyl iron powder or spherical carbonyl iron powder.
3. The method for preparing cobalt-coated carbonyl iron powder according to claim 1, characterized in that: The concentration of the cobalt salt in the cobalt plating solution in step (1) is 10-50 g / L; The concentration of the active agent in the cobalt plating solution in step (1) is 30-60 g / L; The concentration of the complexing agent in the cobalt plating solution in step (1) is 20-100 g / L.
4. The method for preparing cobalt-coated carbonyl iron powder according to claim 1, characterized in that: Step (2) After the cobalt plating solution is heated to 70-90° C., the pH is adjusted to 9.5-10.5 by adding sodium hydroxide; In step (2), the cobalt plating solution is heated to 70-90° C. by water bath heating.
5. The method for preparing cobalt-coated carbonyl iron powder according to claim 1, characterized in that: In the heat preservation reaction of step (2), the pH of the reaction process is controlled to be 9.5-10.5 by adding acidic and alkaline substances, wherein the alkaline substance is at least one of NaOH, KOH, Ca(OH)2 and ammonia water; the acidic substance is at least one of citric acid, acetic acid, dilute HCl, dilute H2SO4 and dilute HNO3.
6. The method for preparing the cobalt-coated carbonyl iron powder according to any one of claims 1 to 5, characterized in that: In step (2), the amount of carbonyl iron powder added to the cobalt plating solution is 5-10 g / L.
7. The method for preparing cobalt-coated carbonyl iron powder according to claim 1, characterized in that: In step (2), the carbonyl iron powder is added under stirring, and the stirring rate is 300-600 rmp; The insulation reaction time in step (2) is 60 to 180 minutes.
8. The method for preparing cobalt-coated carbonyl iron powder according to claim 7, characterized in that: The insulation reaction time in step (2) is 90 to 120 minutes; The specific steps of separating and obtaining the powder in step (3) are as follows: after the heat preservation reaction is completed, distilled water is added to the reaction container, and the iron powder is adsorbed to the bottom of the container by a magnet; then, the distilled water on the upper layer is poured out to separate and retain the iron powder, that is, the powder is separated by a magnet; The washing method in step (3) is: first washing with distilled water and then washing with anhydrous ethanol; the drying in step (3) is vacuum drying.
9. The cobalt-coated carbonyl iron powder prepared by the method for preparing the cobalt-coated carbonyl iron powder according to any one of claims 1 to 8.
10. Use of the cobalt-coated carbonyl iron powder according to claim 9 in preparing microwave absorbing materials.
Citation Information
Patent Citations
Method for coating surface of wave-absorbing material with magnetic metal film
CN110541162A
Nickel plating solution, nickel-coated carbonyl iron powder material and preparation method of nickel-coated carbonyl iron powder material
CN115637427A
Cobalt plating solution, cobalt-coated carbonyl iron powder material and preparation method of cobalt-coated carbonyl iron powder material
CN115679302A
Shielding wave-absorbing powder and preparation method thereof
CN116275027A
Modified carbonyl iron powder as well as preparation method and application thereof
CN116689748A
Cited By
Preparation method and application of ZIF coated plant polyphenol modified carbonyl iron powder wave-absorbing agent
CN121759156A
